2019
DOI: 10.17221/217/2017-swr
|View full text |Cite
|
Sign up to set email alerts
|

The influence of soil texture on the course of volume changes of soil

Abstract: Volume changes of soil associated with soil moisture changes are caused by the presence of clay minerals from illite and montmorillonite groups. Clay minerals are found in the so-called clay soil component which can be quantified by laboratory analysis of the soil particle-size distribution. Consequently, the potential for volume changes in soil can be assessed from soil texture. In our study, 172 soil samples with different textures were used to measure dependencies between volume changes in soil and changes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…The significance of each is as follows. Soil texture (of which the proportion of silt is a component) is regarded an indicator of the extent of land degradation because soil texture influences soil volume (Tall et al, 2019), resistance to soil erosion, and plant growth (Colazo & Buschiazzo, 2010; Su et al, 2015). BD is probably a crucial indicator of soil porosity and aeration (Juhos et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The significance of each is as follows. Soil texture (of which the proportion of silt is a component) is regarded an indicator of the extent of land degradation because soil texture influences soil volume (Tall et al, 2019), resistance to soil erosion, and plant growth (Colazo & Buschiazzo, 2010; Su et al, 2015). BD is probably a crucial indicator of soil porosity and aeration (Juhos et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Clayey soils are also recognized for their distinct volume changes in response to moisture. These changes often result in the formation of cracks and vertical movements in natural conditions [54,55].…”
Section: Soils Identification and Samplingmentioning
confidence: 99%
“…It is essential to recognize that the levels in the observation boreholes represent the piezometric head, rather than the free GWL [4][5], as confirmed by the comprehensive hydrogeological survey conducted in the area. This survey, indicated that the GWL in the region of interest is confined (under pressure).…”
Section: Defining and Obtaining Input Data For Model Specificationmentioning
confidence: 99%